Glycan specificity of P[19] rotavirus and comparison with those of other related P genotypes - Liu,Y; Ramelot,TA; Huang,P; Liu,Y; Li,Z; Feizi,T; Zhong,W; Wu,FT; Tan,M; Kennedy,MA; Jiang,X (Journal of Virology, 2016)
The P[19] genotype belongs to the P[II] genogroup of group A rotaviruses (RVs). However, unlike the other P[II] RVs that mainly infects humans, P[19] RVs commonly infect animals (porcine), making P[19] unique to study RV diversity and host ranges. Through in vitro binding assays and saturation transfer difference (STD) NMR, we found that P[19] could bind mucin cores 2, 4, and 6, as well as type 1 histo-blood group antigens (HBGAs). The common sequences of these glycans serve as minimal binding units, while additional residues, such as the A, B, H, and Lewis epitopes of the type 1 HBGAs, can further define the binding outcomes and therefore, likely the host ranges for P[19] RVs. This complex binding property of P[19] is shared with those of the other three P[II] RVs (P[4], P[6] and P[8]) in that all of them recognized the type 1 HBGA precursor, although P[4] and P[8], but not P[6], also bind to mucin cores. Moreover, while essential for P[4] and P[8] binding, the addition of the Lewis epitope blocked P[6] and P[19] binding to type 1 HBGAs. Chemical shift NMR of P[19] VP8 identified a ligand binding interface that has shifted away from the known RV P-genotype binding sites but is conserved among all P[II] RVs and two P[I] RVs (P[10] and P[12]), suggesting an evolutionary connection among these human and animal RVs. Taken together, these data are important for hypotheses on potential mechanisms for RV diversity, host ranges, and cross-species transmission. IMPORTANCE: In this study, we found that this P[19] strain and other P[II] RVs recognize mucin cores and the type 1 HBGA precursors as the minimal functional units and that additional saccharides adjacent to these units can alter binding outcomes and thereby possibly host ranges. These data may help to explain why some P[II] RVs, such as P[6] and P[19], commonly infect animals but rarely humans, while others, such as the P[4] and P[8] RVs, mainly infect humans and are predominant over other P genotypes. Elucidation